AYAT-AYAT FLEXING DAN KONTEKSTUALISASINYA DALAM KAJIAN PSIKOLOGI: SEBUAH PENDEKATAN TERHADAP FENOMENA PAMER DALAM MEDIA SOSIAL - Masruri, Ahmad (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
This paper explores the phenomenon of "flexing" or showing off found in various verses on social media, and its contextualization from a psychological perspective. This phenomenon not only reflects social and cultural dynamics, but also has profound implications for individual mental health and social behavior. Using theoretical approaches from social and clinical psychology, this paper analyzes the motivation behind flexing, its impact on self-esteem, and how this phenomenon affects social perception and interaction. The method used is quantitative descriptive of the development of psychology to determine the motivation behind this behavior, and its impact on mental health, as well as social media that reinforces this tendency. The results of this study are that Islam emphasizes that showing off behavior is part of riya' (arrogance) which is strictly prohibited. Verses of the Qur'an such as QS Luqman (31:18) and QS Al-Baqarah (2:264) remind people not to be excessively proud of wealth. The concept of Tahadduts bi al-Ni'mah in Islam allows mentioning pleasures on condition that one is not arrogant or riya'. Flexing is also considered an act that can damage social relationships and shows a lack of gratitude to Allah.